Orthodontic Extrusion of Fractured Tooth: A Case Report - Kafle, Dashrath; Shrestha, Reetu; Sapkota, Binam; Acharya, Nisha (Orthodontic Journal of Nepal, 2012)
Trauma to the aesthetic region of the mouth is very common. However the treatment of the traumatic injuries of the tooth depends upon various factors. Orthodontic extrusion of the fractured tooth is regularly practiced treatment modality. Orthodontic extrusion of such tooth is physiological, less invasive and long lasting. The extrusion of the tooth brings enough dental tissue to maintain the biological width and ferrule later into restorative/prosthetic phase. In this article we will report a case which was extruded 4mm after endodontic treatment and restored by crown.